Peran Orang Tua dan Pengembangan Kecerdasan Spiritual Anak - Farok Afero; Setiawan, Bahar Agus; Tamami, Badrut (Jurnal Parenting dan Anak, 2024)
Spiritual intelligence is very important for human life. Efforts to develop this intelligence must start from the parents, because parents are the first to be known by a child, parents are the first madrasah for their child. Objectives: 1) What is the role of parents in developing children's spiritual intelligence in Gambirono Village, Gambirono Kulon Hamlet) What are the supporting and inhibiting factors for the role of parents in developing children's spiritual intelligence in Gambirono Village, Gambirono Kulon Hamlet. Method: The approach and type used in this research is descriptive qualitative field. The research subjects are: Parents, children, TPQ teachers, religious figures in Gambirono Village, Gambirono Kulon Hamlet. Data collection techniques are interviews, observation, documentation. Data analysis techniques use data reduction, data presentation, verification, while data validity uses technical triangulation and source triangulation. Conclusion: The role of parents is very important for human life, in developing children's spiritual intelligence.